Hubungan Pengetahuan Ibu dan Dukungan Suami dengan Pemberian Imunisasi Rotavirus pada Bayi di Kelurahan Merjosari Kota Malang - Azizah Nurhasanah; Reni Wahyu Triningsih; Gita Kostania (STIKES Columbia Asia Medan, 2025)
Indonesian people's understanding of immunization and early detection is still different, so babies and toddlers have not received immunizations in health services. Husband's support has an important role in providing support and motivation so that mothers come to every posyandu activity. Data from the 2020 Indonesian Health Profile shows that diarrhea is the second largest contributor to death after pneumonia (lung infection) in babies aged 29 days - 11 months, namely 9.8% and in the group of toddlers aged 12-59 months, 4.5% of total deaths. . The aim of the research is to determine the relationship between maternal knowledge and husband's support with the provision of Rotavirus immunization in Merjosari Village, Malang City. The research design is an analytical method with a cross sectional approach which was carried out on a sample of 80 respondents in Merjosari Village, Malang City. The data collection tools used were a mother's knowledge questionnaire with 17 question items, a husband's support questionnaire with 12 statement items. The results of research on maternal knowledge showed that of the 80 respondents, the majority of mothers' knowledge was good with 52 respondents (65%) being given rotavirus immunization. The results of the Chi-Square test in this study show that there is a relationship between maternal knowledge and immunization for babies in Merjosaroi Village, Malang City with a value of p=0.000; 0.05. The results of research on husband's support showed that of the 80 respondents, the majority supported rotavirus immunization, 61 respondents (76.3%). The results of the Chi-Square test in this study show that there is a relationship between saumi support and immunization for babies in Merjosaroi Village, Malang City with a value of p=0.001; 0.05. Based on the results of this research, community health centers and cadres can carry out the activities needed to increase mothers' knowledge about rotavirus immunization and husband support, such as providing counseling to mothers, holding programs that demonstrate immunization activities and encouraging mothers to come to the posyandu for immunization.